2016
DOI: 10.1002/sia.5957
|View full text |Cite
|
Sign up to set email alerts
|

ToF‐SIMS depth profiles on Argon‐implanted amorphous carbon. Damage effect and hydrogen characterization

Abstract: Any noble gas characterization that includes chemical ionization for the detection process is hard to manage because of the very high ionization potential: the range is from 10 to 25eV; electronic affinity is also close to zero. So ionization processes used in secondary ion mass spectroscopy (SIMS) analysis have very poor cross section. It is known that amorphous carbon mechanical properties are changed by implant; sp2/sp3 ratio and H content in the film are modified, allowing high density and good transparenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…This C n species is usually detected in carbonized compounds, such as graphite and amorphous carbon. 25,26) These results indicate that FIB irradiation destroyed P6T molecules to form a carbonized layer with gallium deposition on the top of the crystal surface. We concluded that quenching of emission from the crystal surface occurs due to the above chemical transformation.…”
mentioning
confidence: 90%
“…This C n species is usually detected in carbonized compounds, such as graphite and amorphous carbon. 25,26) These results indicate that FIB irradiation destroyed P6T molecules to form a carbonized layer with gallium deposition on the top of the crystal surface. We concluded that quenching of emission from the crystal surface occurs due to the above chemical transformation.…”
mentioning
confidence: 90%
“…Также достаточно очевиден выбор линий вторичных ионов при молекулярном анализе, где используются линии молекул [7,8] или их наиболее тяжелых фрагментов [9]. В массспектре углеродсодержащих материалов присутствует несколько десятков линий кластерных вторичных ионов с высокой интенсивностью, и вопрос его обработки для анализа концентрации s p 2 -и s p 3 -гибридных состояний углерода до сих пор не решен, хотя первые работы по анализу таких материалов появились более десяти лет назад [10][11][12]. Целью настоящей работы является поиск нового варианта обработки масс-спектров ВИМС для определения концентрации N(s p 2 ), N(s p 3 ).…”
unclassified